The democratic leader how democracy defines, empowers and limits its leaders - Kane, John, 1945 Apr. 18-; Patapan, Haig, 1959- (Oxford : Oxford University Press, 2012)
Democratic leadership is the most familiar form of leadership and yet the least well understood by people in democratic countries. This text explores the tensions and dilemmas that beset such leadership in order to explain why democracies produce simultaneously the strongest and weakest of leaders.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Political leadership; Democracy